Adverse drug events observed with intrathecal magnesium sulfate as an adjuvant to bupivacaine for spinal anesthesia in patients undergoing elective cesarean section: a meta-analysis - Yuanhui Zhang; Yan Huang; Jun Li (BMC Pharmacology and Toxicology)
Abstract Introduction Today, the number of cesarean section has drastically increased. Newer scientific reports have shown Magnesium sulfate (MgSO4) to have favorable outcomes for anesthesia. In this analysis, we aimed to systematically compare the adverse drug events observed with intrathecal MgSO4 as an adjuvant to bupivacaine for spinal anesthesia in patients undergoing elective cesarean section. Methods MEDLINE, EMBASE, Web of Science, Google scholar, http://www.ClinicalTrials.gov , and the Cochrane database were searched for relevant publications comparing the adverse drug events observed with intrathecal MgSO4 as an adjuvant to bupivacaine for spinal anesthesia in patients undergoing elective cesarean section. The RevMan software version 5.4 was used to analyze data in this analysis. Risk ratios (RR) with 95% confidence intervals (CIs) were used to represent analysis for the dichotomous data whereas weighted mean difference (WMD) with 95% CI was used to represent results using continuous data. Heterogeneity was assessed by the Q statistic and the I2 statistic tests. Results Eleven studies with a total number of 895 participants were included in this analysis whereby 466 patients were assigned to intrathecal MgSO4 and 429 participants were assigned to a control group. The main results of this analysis show that intrathecal MgSO4 as an adjuvant to bupivacaine was associated with a significantly lower risk of shivering (RR: 0.63, 95% CI: 0.48 – 0.83; P = 0.001). In addition, the risks for hypotension (RR: 1.11, 95% CI: 0.86 – 1.44; P = 0.40), nausea and vomiting (RR: 1.08, 95% CI: 0.76 – 1.54; P = 0.65), pruritus (RR: 0.77, 95% CI: 0.51 – 1.17; P = 0.22), and bradycardia (RR: 4.45, 95% CI: 0.97 – 20.36; P = 0.05) were not significantly increased. The sensory (WMD: 23.15, 95% CI: 7.83 – 38.48; P = 0.003), and motor block duration (WMD: 24.29, 95% CI: 16.36 – 32.23; P = 0.00001) and the duration of spinal anesthesia (WMD: 29.24, 95% CI: 13.61 – 44.87; P = 0.0002) were significantly in favor of MgSO4. Conclusion Intrathecal MgSO4 as an adjuvant to bupivacaine was associated with a significantly lower risk of shivering without causing any increase in other adverse drug events in patients undergoing elective cesarean section. Efficacy outcomes were also appreciated. Larger studies should be able to confirm this hypothesis.